Overfat and Underfat: New Terms and Definitions Long Overdue - Maffetone, Philip B.; Rivera-Dominguez, Ivan; Laursen, Paul B. (Frontiers in Public Health, 2017)
For the first time in human history, the number of obese people worldwide now exceeds those who are underweight. However, it is possible that there is an even more serious problem—an overfat pandemic comprised of people who exhibit metabolic health impairments associated with excess fat mass relative to lean body mass. Many overfat individuals, however, are not necessarily classified clinically as overweight or obese, despite the common use of body mass index as the clinical classifier of obesity and overweight. The well-documented obesity epidemic may merely be the tip of the overfat iceberg. The counterpart to the overfat condition is the underfat state, also a common and dangerous health circumstance associated with chronic illness and starvation. Currently (and paradoxically), high rates of obesity and overweight development coexist with undernutrition in developing countries. Studies in cognitive linguistics suggest that accurate, useful, and unintimidating terminology regarding abnormal body fat conditions could help increase a person’s awareness of their situation, helping the process of implementing prevention and simple remedies. Our contention is that promoting the terms “overfat” and “underfat” to describe body composition states to the point where they enter into common usage may help in creating substantive improvements in world health.